Identificação e estudo das áreas prioritárias para conservação da biodiversidade no Sinclinal Moeda (MG) com base nos serviços ecossistêmicos - Denise Maria Lopes Formoso (2013)
Mountains are important sources of water, energy and biological diversity. They are also considered centres of biodiversity and endemism for exhibiting diverse ecosystems due to their large topographic variation. In this context lies the Moeda Syncline, with an expressive identity within the Quadrangle located south of Belo Horizonte. This geological formation with its numerous variations of soil, altitudes and climates gives rise to a mosaic of vegetal phytophysionomy which, together with its characteristic fauna, harbour a large number of endemic, rare and endangered species of importance for conservation. The Syncline also stands out for its regional hydrological importance, sheltering underground reserves and significant areas for recharge of water sources. However, the urban sprawl of Belo Horizonte toward this mountainous environment, along with the intensification of mining activities, pose threats to biodiversity and ecosystem services. Thus, this study aims to identify and study the priority areas for biodiversity conservation within the Moeda Syncline on the basis of ecosystem services. Therefore, services related to water, erosion control, biodiversity and tourism were surveyed, mapped and selected, generating spatialized information that were used in a multi-criteria analysis with the support of the modelling software DINAMICA. Weighting was elaborated through direct consultation of Moeda Syncline experts. As a result a map was generated by superposition and prioritization of environmental services with indications of priority areas for conservation. The data point to the prioritization of areas of higher elevations with steep slopes located along the ridges formed by the edges of the Syncline. In these areas the geological layer containing the main aquifers and ecosystems on canga known as the Cauê formation is predominant. Lower priority areas for conservation are associated with urban occupations, mining areas and other areas with exposed soil. Despite the presence of several water routes, these areas, compared to the rest of the Syncline are lower in altitude, have softer declivities and present less vulnerability to soil erosion. Given the expansion tendency of mining activities and urban occupation in an area with a rich biodiversity and fragile environments, the creation of protected areas is an important initiative for the conservation of natural ecosystems. With a view to create new protected areas, the identification and understanding of ecosystem services in the Syncline may be another factor to consider in addition to the conservation of fauna and flora.